The TERPADU Model: Integrating Cognitive, Contextual, and Spiritual Dimensions in Islamic Education - Nila Lukmatus Syahidah; Titin Widya Risni; Vieta Karina; Mahrukh Siddiqui (Edudeena : Journal of Islamic Religious Education, 2026)
This study aims to examine the implementation of the TERPADU model as an integrative framework that unifies cognitive, contextual, and spiritual dimensions in Islamic Education (PAI) at the elementary school level. Employing a qualitative approach with a case study design, the research explores how the TERPADU model is enacted in classroom practices and how it facilitates meaningful learning experiences. The model is operationalized through seven sequential stages: Telaah (critical examination of concepts), Eksplorasi (active inquiry and knowledge discovery), Rumuskan (formulation of understanding), Presentasikan (communication of ideas), Aplikasikan (contextual application), Dunia (connection to real-life contexts), and Ukhrowi (internalization of spiritual values). Data were collected through classroom observations, interviews, and document analysis, and were analyzed using an interactive model of data condensation, data display, and conclusion drawing. The findings indicate that the TERPADU model effectively promotes holistic student engagement by integrating cognitive understanding, contextual relevance, and spiritual awareness. Furthermore, the model supports value internalization and fosters students’ reflective and meaningful learning processes. The implications of this study suggest that the TERPADU model can serve as a practical pedagogical framework for teachers to design integrative PAI learning, as well as a conceptual reference for developing value-based and student-centered instructional models in Islamic education. Keywords: TERPADU model; Islamic Religious Education; student engagement; cognitive, contextual, and spiritual integration; value internalization; elementary education.